Health and economic implications of harmful cultural practices (HCPs) against women and girls in Ebonyi State: (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This empirical study examines the impact of nine harmful cultural practices (HCPs) on the health and economic well-being of women and girls in Ebonyi State, Nigeria. Using Social Determinant of Health and Feminist theories, the study explores how cultural norms and gender-based inequities influence women’s health and economic opportunities, shaping broader social and economic outcomes. A mixed-methods approach was employed to collect primary data from 99 respondents, assessing their awareness of HCPs and their effects on survivors. The findings reveal that women and girls face significant health challenges, including Vesico Vaginal Fistula (VVF), prolonged labor, painful sex, and multiple sex partners. Economically, HCPs contribute to dependency, poverty, lack of education, and poor nutrition. These practices have exacerbated the suffering of many women and marginalized children. The study calls for targeted sensitization efforts by human rightsadvocates, particularly in rural areas, and urges policymakers to enact laws prosecuting those who perpetuate these harmful practices.
Keywords: Harmful cultural practices; Women; Girls; Health; Economic